Wireless Power Transfer to a Microaerial Vehicle with a Microwave Active Phased Array - Shotaro Nako; Kenta Okuda; Kengo Miyashiro; Kimiya Komurasaki; Hiroyuki Koizumi (International Journal of Antennas and Propagation)
A wireless power transfer system using a microwave active phased array was developed. In the system, power is transferred to a circling microaerial vehicle (MAV) by a microwave beam of 5.8 GHz, which is formed and directed to the MAV using an active phased array antenna. The MAV is expected to support observation of areas that humans cannot reach. The power beam is formed by the phased array with eight antenna elements. Input power is about 5.6 W. The peak power density at 1,500 mm altitude was 2.63 mW/cm2. The power is sent to a circling MAV. Therefore, the transfer beam should be polarized circularly to achieve a constant power supply independent of its yaw angle. To minimize the polarization loss, a sequentially routed antenna (SRA) was applied to the transmitter antenna. Results show that the axial ratio of 0.440 dB was accomplished and that power fluctuation was kept below 1%.